The Effectiveness of a Proposed Training Program in Developing Idiomatic Translation Skills and Attitudes towards the Figurative Language among Non-Specialist Students of English - ماجد محمدين (Maǧallaẗ Kulliyyaẗ Al-Tarbiyyaẗ - Ǧamiʿaẗ Būr Saʿīd, 2022)
English is crowded with figurative language expressions that do not mean precisely what they say. An idiom is a figurative expression that cannot be interpreted literally or translated word for word. Based upon, investigating idiomatic translation skills is an issue worth examining because of their significance in helping EFL students interpret and translate the figurative language expressions in a correct understandable language that maintains translation quality and its intended meanings. However, these skills have not been investigated extensively. The aim of this study was to investigate the effectiveness of a proposed training program in developing idiomatic translation skills and attitudes towards the figurative language among non-specialist students of English. A descriptive analytical method and an experimental method with a two-group design were used to investigate the variables of this study, which was conducted with 60 non-specialist students of English enrolled in the second level at Port Said Faculty of education, randomly assigned into a control group (N=30) and an experimental group (N=30). The data were collected using a list of idiomatic translation skills, an achievement test, and a scale on participants’ attitudes toward the figurative language. The experimental group received the proposed training program that included (20) sessions and lasted for (10) weeks in the first semester of the academic year 2019/2020.